Grouping of Regencies/Municipalities in Eastern Indonesia in 2021 Based on Socio-Economic Indicators - Annisa Firnanda; Arie Wahyu Wijayanto (Sistemasi: Jurnal Sistem Informasi, 2023)
Differences in social, economic, demographic and resource conditions in each region can cause inequality, so it is necessary to encourage economic development according to the capabilities of the region. The importance of looking at socio-economic indicators that are development targets, especially in Eastern Indonesia (KTI). This study uses two non-hierarchical methods, namely K-Means and K-Medoids. In this study, Principal Component Analysis (PCA) was carried out to produce 3 factors. Determining the number of clusters using internal validity and stability shows that the K-Means method with a number of clusters of 2 produces the most optimal clusters. Cluster 1 consists of 152 regencies/municipalities, while cluster 2 consists of 80 regencies/municipalities. Cluster 1 has above average infrastructure and economic characteristics, while its human quality is still below average.